Injection vs micro-injection molding of nano-particle filled polyamide 6: Moldability and structuring. (16th September 2021) - Surace, Rossella; Pagano, Claudia; Bellantone, Vincenzo; Gatti, Simone; Castellani, Leonardo; Vighi, Massimo; Stoclet, Grégory; Sechi, Sara; Fassi, Irene; Baldi, Francesco
Abstract: In this work, the moldability via micro-injection molding (μIM) of nano-filled polyamide 6 (PA6) based systems and the microstructural characteristics of the micro-injected parts were investigated and compared to those observed via traditional injection molding (IM). Two types of nano-fillers, different in nature and geometry, were examined, namely carbon nanotubes and silicate layers. The presence of nano-fillers did not impair the mold replication capability of PA6 in the μIM process. A micro-rib and a standard dumbbell specimen for tensile tests were used as reference micro- and macro-injected part, respectively. Transmission Electron Microscopy, Wide and Small Angle X-ray Scattering and Differential Scanning Calorimetry analyses showed that, due to the different thermomechanical histories during μIM and IM, the micro- and the macro-parts have different microstructures, influenced also by the filler type. Both nano-filler dispersion and PA6 crystallinity were influenced. Graphical abstract: Image 1 Highlights: Traditional and μ-injection molding of nano-filled polyamide 6 are compared. Nano-fillers do not impair μ-mold replication capability of polyamide 6. μ-injection promotes organo-clay fragmentation and exfoliation in polyamide 6. μ-injection affects orientation of organo-clay particles in polyamide 6-based parts. Nano-fillers in polyamide 6 can affect largely the μ-part polymer crystallinity.